The evolution in the surgical management of Peyronie's disease. Issue 2 (May 2021) - Colombo, Fulvio; Franceschelli, Alessandro; Gentile, Giorgio; Droghetti, Matteo; Fiorillo, Alessandro; Palmisano, Franco
Peyronie's disease (PD) is due to a fibrotic alteration of the tunica albuginea of the penis. It is responsible of penile pain, angulation, and possible erectile dysfunction (ED). Despite almost three centuries have passed since the first description of the disease, etiology still remains uncertain. This fact has led to the lack of a truly effective medical therapy and to date the surgical treatment, although not yet standardized, is the only one that offers acceptable outcomes in terms of function and overall patient's satisfaction. Since the beginning of the surgical experience in this field, two different currents of thought have developed: the first, involved the proposal of a number of different plication techniques, applied on the healthy side of the penis, opposite to the sick side, with the sole purpose of correcting the curvature; on the other side, efforts have focused on treating the "focus" of the disease, thus developing the so called "plaque surgery." If with the passing of the decades neither of the two "philosophical" currents has prevailed, this probably depends on the fact that is still not clear which is the lesser of evils: the frequent onset of ED which may follows the plaque surgery or rather the penis shortening that inevitably occurs if any technique of plication has been applied. Our contribution aims to offer an historical retrospective of the surgical treatment of this disease as well as to discuss the latest international guidelines on this topic. The reader will also find some notes about our personal experience in this field.